Structure Social Group Attachment measure (Journal Of Educational and Psychological Researches, 2023)
This study aims to answer the following question: Is a student who attaches to the social group strongly affected by social interaction and social status?  The population of the study included a group of medical students at the University of Al-Kufa. To collect the required data, a scale of Social Group Attachment consisting of (25) items was administered to a sample of (600) students, (257) male students, and (343) female students. The results revealed that students do not have a high level of attachment to the social group and they have a fear of that. There are no significant differences between the levels of attachment between males and females. There are no significant differences regarding colleges, the four academic levels, and social status.